2018
DOI: 10.1038/ajg.2017.469
|View full text |Cite
|
Sign up to set email alerts
|

ACG Clinical Guideline: Alcoholic Liver Disease

Abstract: Alcoholic liver disease (ALD) comprises a clinical-histologic spectrum including fatty liver, alcoholic hepatitis (AH), and cirrhosis with its complications. Most patients are diagnosed at advanced stages and data on the prevalence and profile of patients with early disease are limited. Diagnosis of ALD requires documentation of chronic heavy alcohol use and exclusion of other causes of liver disease. Prolonged abstinence is the most effective strategy to prevent disease progression. AH presents with rapid ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
634
0
38

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(680 citation statements)
references
References 189 publications
8
634
0
38
Order By: Relevance
“…Each organ used for a patient with severe AH is an organ not used for a suffering patient with CLD. Again, perhaps sensitive to this concern, proponents of this practice frequently cite that early LT for AH accounts for “only 1.5%‐3% of the organ pool.” However, these estimations are derived from the earliest pilot studies in which only a tiny portion of eligible patients with AH underwent transplantation. As the practice of early LT for AH expands and has now emerged in guidelines as a standard of care option for highly selected candidates, these earlier projections underestimate how the donor pool will be affected .…”
Section: Utilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Each organ used for a patient with severe AH is an organ not used for a suffering patient with CLD. Again, perhaps sensitive to this concern, proponents of this practice frequently cite that early LT for AH accounts for “only 1.5%‐3% of the organ pool.” However, these estimations are derived from the earliest pilot studies in which only a tiny portion of eligible patients with AH underwent transplantation. As the practice of early LT for AH expands and has now emerged in guidelines as a standard of care option for highly selected candidates, these earlier projections underestimate how the donor pool will be affected .…”
Section: Utilitymentioning
confidence: 99%
“…Again, perhaps sensitive to this concern, proponents of this practice frequently cite that early LT for AH accounts for “only 1.5%‐3% of the organ pool.” However, these estimations are derived from the earliest pilot studies in which only a tiny portion of eligible patients with AH underwent transplantation. As the practice of early LT for AH expands and has now emerged in guidelines as a standard of care option for highly selected candidates, these earlier projections underestimate how the donor pool will be affected . And it should be noted that early LT for AH eliminates the possibility that a patient might recover without a transplant and will correspondingly increase the number of organs extracted from the donor pool; if this percentage is indeed 20%‐40%, then out of every five transplants performed for early LT in AH, at least one to two organs are used unnecessarily.…”
Section: Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, corticosteroids were considered a convincingly effective therapeutic intervention for patients with autoimmune hepatitis (AIH) . If there are no contraindications, corticosteroids should also be used in patients with severe alcoholic hepatitis (AH) . Since most studies indicated that the administration of corticosteroids was beneficial to only a few severe AH patients, early recognition of the non‐responders using the Lille score is important to limit unnecessary exposure …”
Section: History and Current Status Of Corticosteroid Use In Liver DImentioning
confidence: 99%
“…Alcohol‐related liver disease (ALD) is a leading cause of liver failure, is increasing in prevalence, and is a leading cause of mortality . ALD occurs in the setting of underlying alcohol use disorder (AUD) and broadly encompasses a pathological and clinical spectrum ranging from asymptomatic steatosis to acute alcohol‐related hepatitis (AH) to decompensated cirrhosis with or without hepatocellular carcinoma . Current medical interventions are of limited efficacy and focus on the treatment of AH.…”
Section: Proposed Comprehensive Ald Data Collection Toolmentioning
confidence: 99%